2002
DOI: 10.1006/viro.2002.1596
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Charge-to-Alanine Mutagenesis of Human Respiratory Syncytial Virus L Polymerase Generates Temperature-Sensitive Viruses

Abstract: Clustered charge-to-alanine mutagenesis was performed on the large (L) polymerase protein of human respiratory syncytial virus to identify charged residues in the L protein that are important for viral RNA synthesis and to generate temperature-sensitive viruses. Clusters of three, four, and five charged residues throughout the entire L protein were substituted with alanines. A minigenome replicon assay was used to determine the functions of the mutant L proteins and to identify mutations that caused temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…VUSB5 and VUSB6 RNA molecule were assayed for their capacity to produce viruses in two independent experiments, both of which showed the same result. It has been reported that charge-to-alanine mutagenesis of viral proteins may generate temperaturesensitive mutants (Hanley et al, 2002;Hassett and Condit, 1994;Tang et al, 2002). In the current study, nsp1 mutants VUSB5, VUSB6, and nsp1DMid did not exhibit temperature-sensitive phenotypes as no infectious virus was recovered at either 37 -C or 32 -C. The nsp1DFL virus was not tested at 32 -C.…”
Section: Charge-to-alanine Mutagenesis Of the Nsp1 Amino-terminusmentioning
confidence: 50%
“…VUSB5 and VUSB6 RNA molecule were assayed for their capacity to produce viruses in two independent experiments, both of which showed the same result. It has been reported that charge-to-alanine mutagenesis of viral proteins may generate temperaturesensitive mutants (Hanley et al, 2002;Hassett and Condit, 1994;Tang et al, 2002). In the current study, nsp1 mutants VUSB5, VUSB6, and nsp1DMid did not exhibit temperature-sensitive phenotypes as no infectious virus was recovered at either 37 -C or 32 -C. The nsp1DFL virus was not tested at 32 -C.…”
Section: Charge-to-alanine Mutagenesis Of the Nsp1 Amino-terminusmentioning
confidence: 50%
“…Apart from deleting non-essential genes, it is also possible to target a specific protein and replace charged amino acids with noncharged ones. This has been done with the HRSV L protein and a number of the mutations were attenuating [129]. Another strategy is to alter the order of the viral genes.…”
Section: Other Strategies For the Development Of Live Attenuated Brsvmentioning
confidence: 99%
“…This is a common recombinant strategy to develop mutant proteins. This was done with the L protein, and a number of such mutations were successfully recovered in virus (30). Some of these were attenuated, thus adding to panel of point mutations available to attenuate RSV.…”
Section: Identifying Mutations That Attenuate Rsvmentioning
confidence: 99%